Molecular Hallmarks, Agronomic Performances and Seed Nutraceutical Properties to Exploit Neglected Genetic Resources of Common Beans Grown by Organic Farming in Two Contrasting Environments - Sica, Pietro; Scariolo, Francesco; Galvao, Aline; Battaggia, Domiziana; Nicoletto, Carlo; Maucieri, Carmelo; Palumbo, Fabio; Franklin, Dorcas; Cabrera, Miguel; Borin, Maurizio; Sambo, Paolo; Barcaccia, Gianni (Frontiers in Plant Science, 2021)
Common bean (Phaseolus vulgaris L.) is an essential source of food proteins and an important component of sustainable agriculture systems around the world. Thus, conserving and exploiting the genetic materials of this crop species play an important role in achieving global food safety and security through the preservation of functional and serependic opportunities afforded by plant species diversity. Our research aimed to collect and perform agronomic, morpho-phenological, molecular-genetic, and nutraceutical characterizations of common bean accessions, including lowland and mountain Venetian niche landraces (ancient farmer populations) and Italian elite lineages (old breeder selections). Molecular characterization with SSR and SNP markers grouped these accessions into two well-separated clusters that were linked to the original Andean and Mesoamerican gene pools, which was consistent with the outputs of ancestral analysis. Genetic diversity in the two main clusters was not distributed equally-the Andean gene pool was found to be much more uniform than the Mesoamerican pool. Additional subdivision resulted in subclusters, supporting the existence of six varietal groups. Accessions were selected according to preliminary investigations and historical records and cultivated in two contrasting Venetian environments: sea-level and mountain territories. We found that the environment significantly affected some nutraceutical properties of the seeds, mainly protein and starch contents. The antioxidant capacity was found significantly greater at sea level for climbing accessions and in the mountains for dwarf accessions. The seed yield at sea level was halved than mountain due to a seeds reduction in weight, volume, size and density. At sea level, bean landraces tended to have extended flowering periods and shorter fresh pod periods. The seed yield was positively correlated with the length of the period during which plants had fresh pods and negatively correlated with the length of the flowering period. Thus, the agronomic performance of these genetic resources showed their strong connection and adaptation to mountainous environments. On the whole, the genetic-molecular information put together for these univocal bean entries was combined with overall results from plant and seed analyses to select and transform the best accessions into commercial varieties (i.e. pure lines) suitable for wider cultivation.